Whether high government subsidies reduce the healthcare provision of township healthcare centers in rural China - Chi Shen; Zhongliang Zhou; Sha Lai; Wanyue Dong; Yaxin Zhao; Dan Cao; Dantong Zhao; Yangling Ren; Xiaojing Fan (BMC, 2021)
Abstract Background China's government launched a large-scale healthcare reform from 2009. One of the main targets of this round reform was to improve the primary health care system. Major reforms for primary healthcare institutions include increasing government investment. However, there are insufficient empirical studies based on large sample to catch long-term effect of increased government subsidy and lack of sufficient incentives on township healthcare centers (THCs), therefore, this study aims to provide additional empirical evidence on the concern by conducting an empirical analysis of THCs in Shaanxi province in China. Methods We collected nine years (2009 to 2017) data of THCs from the Health Finance Annual Report System (HFARS) that was acquired from the Health Commission of Shaanxi Province. We applied two-way fixed effect model and continue difference-in-difference (DID) model to estimate the effect of percentage of government subsidy on medical provision. Results A clear jump of the average percentage of government subsidy to total revenue of THCs can be found in Shaanxi province in 2011, and the average percentage has been more than 60% after 2011. Continue DID models indicate every 1% percentage of government subsidy to total revenue increase after 2011 resulted in a decrease of 1.1 to 3.5% in THCs healthcare provision (1.9% in medical revenue, 1.2% in outpatient visit, 3.5% in total occupy beds of inpatient, 1.1% in surgery revenue, 2.1% in sickbed utilization rate). The results show that the THCs with high government subsidy reduce the number of medical services after 2011. Conclusions We think that it is no doubt that the government should take more responsibility for the financing of primary healthcare institutions, the problem is when government plays a central role in the financing and delivery of primary health care services, more effective incentives should be developed.